2011
DOI: 10.1097/brs.0b013e3181e531a1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Predictive Factors Relating to Prognosis of Conservative and Surgical Treatments for Cervical Spondylotic Amyotrophy

Abstract: The present study has demonstrated the outcome of conservative and of surgical treatments for CSA, together with the predictive factors relating to the prognosis. Conservative treatment should be initially tried on CSA patients, especially those with predictive factors relating to a better prognosis. However, if conservative treatment failed, surgical intervention was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Therefore, based on our results, it was considered that the presence of the pyramidal tract sign can be used as a poor prognostic factor in surgically treated CSA patients. However, Inui et al 11 reported that the pyramidal tract sign was not associated with the prognosis, not only in conservatively treated patients, but also in surgically treated patients. Although further investigations will be needed to explain the inconsistencies between the studies, the differences in the regimen used for conservative management may be at least partly responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on our results, it was considered that the presence of the pyramidal tract sign can be used as a poor prognostic factor in surgically treated CSA patients. However, Inui et al 11 reported that the pyramidal tract sign was not associated with the prognosis, not only in conservatively treated patients, but also in surgically treated patients. Although further investigations will be needed to explain the inconsistencies between the studies, the differences in the regimen used for conservative management may be at least partly responsible.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no significant differences in the course of disease and high intensity zone on the T2-weighted MRI between the two types. Similarly, Inui et al 16. found no statistical difference in surgical outcomes between disease types and sites of compression.…”
Section: Discussionmentioning
confidence: 93%
“…First, symptoms in some patients with the proximal type of CSA have resolved spontaneously or with conservative treatment such as neck traction, which allowed the patients to avoid invasive treatment. Secondly, there is a possibility that these patients may actually have a motor neuron disease such as ALS, and treating [7] reported that patients who fulfilled predictive factors such as age \50 years old, duration of symptoms \6 months, single-level stenosis, foraminal stenosis and a good response to traction therapy improved with conservative treatment. On the other hand, other studies reported that conservative treatment may be effective, but complete resolution cannot be expected [2,8,9].…”
Section: Discussionmentioning
confidence: 98%